2011
DOI: 10.1002/ijc.26119
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic downregulation of c‐FLIPL restores juxtacrine death receptor‐mediated apoptosis in cancer cells in a peritoneal carcinomatosis model

Abstract: Metastasis occurs when circulating cancer cells implant in normal secondary tissues. Paradoxically, many cancer cells express death receptors while many normal tissues express the cognate death receptor ligands, suggesting that cancer cells possess mechanisms to inhibit death receptor signaling. Pharmacological restoration of juxtacrine‐mediated death receptor signaling could prevent cancer cells from implanting in normal tissues such as the peritoneum. The results showed that BAY 11‐7085 significantly inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Additionally, some of the agents that their combined using with TRAIL has been acceptable outcomes but in limited cell lines have been listed below. kurarinone (Seo et al, ; Zhou, Cao, Wang, & Wu, ), monensin (Yoon et al, ), paxiline (Kang et al, ), diclofenac/hyaluronic acid (Dic/HA) (Fecker et al, ), nickel2+ (Schmidt et al, ), SHetA2 (Lin et al, ), BAY 11–7085 (Shen et al, ), compound c (Jang et al, ), FAK inhibitor PH11 (Dao et al, ), caffeic acid phenethyl ester (CAPE) (Li, Wu, et al, ), fasudil (Wang et al, ), cathepsin S inhibitor ZFL (Seo et al, ), 4‐(4‐Chloro‐2‐methylphenoxy)‐N‐hydroxybutanamide (CMH) (Bijangi‐Vishehsaraei, Huang, Safa, Saadatzadeh, & Murphy, ), actinomycin (Haimerl, Erhardt, Sass, & Tiegs, ), H1 (derivative of tetrandrine) (Lin, Wang, et al, ), genistein (Siegelin, Siegelin, Habel, & Gaiser, ), icaritin (Han, Xu, et al, ), ABT‐737 and VX–680 (Choi et al, ), 6‐shogaol (Han, Woo, et al, ), cathepsin E (Yasukochi, Kawakubo, Nakamura, & Yamamoto, ), ozarelix (Festuccia et al, ), transglutaminase 2 inhibitor (TGM2I) (Li, Xu, Bai, Chen, & Lin, ), amurensin G (Kim, Kim, Lee, et al, ), volasertib (Jeon et al, ), temozolomide (TMZ) (Zhitao, Long, Jia, Yunchao, & Anhua, ), chalcone‐24 (Xu et al, ), gingerol (Lee, Kim, Jung, Lee, & Park, ), triptolide (Chen et al, ), AKT inhibitor API‐1 (Li, Ren, et al, ), smac mimetic compounds (SMC) (Cheung et al, ), dicoumarol (Park, Min, Choi, & Kwon, ), partenolide (Trang et al, ), Pyrrolo‐1, 5‐benzoxazepine (PBOX) (Nathwani et al, ), embelin (Siegelin, Gaiser, & Siegelin, ), myricetin (Siegelin, Gaiser, Habel, & Siegelin, ), quercetin (Jung, Heo, Lee, Kwon, & Kim, ), silibinin (Son et al, ), epigallocatechin gallate (EGCG) (Abou El Naga et al, ), icariside II (Du et al, ), anisomycin (Seo et al, ), dioscin (Kim, Kim, Park, et al, ), celecoxib (Chen et al, ), micro RNA 126 (MiR‐126) (Zhang, Zhou, Zhu, & Yuan, ), gambognic acid (Ye et al, ), survivin inhibitor YM155 (Woo, Min, Seo, &...…”
Section: Intracellular Anti‐apoptotic Proteins As Targeted Therapymentioning
confidence: 99%
“…Additionally, some of the agents that their combined using with TRAIL has been acceptable outcomes but in limited cell lines have been listed below. kurarinone (Seo et al, ; Zhou, Cao, Wang, & Wu, ), monensin (Yoon et al, ), paxiline (Kang et al, ), diclofenac/hyaluronic acid (Dic/HA) (Fecker et al, ), nickel2+ (Schmidt et al, ), SHetA2 (Lin et al, ), BAY 11–7085 (Shen et al, ), compound c (Jang et al, ), FAK inhibitor PH11 (Dao et al, ), caffeic acid phenethyl ester (CAPE) (Li, Wu, et al, ), fasudil (Wang et al, ), cathepsin S inhibitor ZFL (Seo et al, ), 4‐(4‐Chloro‐2‐methylphenoxy)‐N‐hydroxybutanamide (CMH) (Bijangi‐Vishehsaraei, Huang, Safa, Saadatzadeh, & Murphy, ), actinomycin (Haimerl, Erhardt, Sass, & Tiegs, ), H1 (derivative of tetrandrine) (Lin, Wang, et al, ), genistein (Siegelin, Siegelin, Habel, & Gaiser, ), icaritin (Han, Xu, et al, ), ABT‐737 and VX–680 (Choi et al, ), 6‐shogaol (Han, Woo, et al, ), cathepsin E (Yasukochi, Kawakubo, Nakamura, & Yamamoto, ), ozarelix (Festuccia et al, ), transglutaminase 2 inhibitor (TGM2I) (Li, Xu, Bai, Chen, & Lin, ), amurensin G (Kim, Kim, Lee, et al, ), volasertib (Jeon et al, ), temozolomide (TMZ) (Zhitao, Long, Jia, Yunchao, & Anhua, ), chalcone‐24 (Xu et al, ), gingerol (Lee, Kim, Jung, Lee, & Park, ), triptolide (Chen et al, ), AKT inhibitor API‐1 (Li, Ren, et al, ), smac mimetic compounds (SMC) (Cheung et al, ), dicoumarol (Park, Min, Choi, & Kwon, ), partenolide (Trang et al, ), Pyrrolo‐1, 5‐benzoxazepine (PBOX) (Nathwani et al, ), embelin (Siegelin, Gaiser, & Siegelin, ), myricetin (Siegelin, Gaiser, Habel, & Siegelin, ), quercetin (Jung, Heo, Lee, Kwon, & Kim, ), silibinin (Son et al, ), epigallocatechin gallate (EGCG) (Abou El Naga et al, ), icariside II (Du et al, ), anisomycin (Seo et al, ), dioscin (Kim, Kim, Park, et al, ), celecoxib (Chen et al, ), micro RNA 126 (MiR‐126) (Zhang, Zhou, Zhu, & Yuan, ), gambognic acid (Ye et al, ), survivin inhibitor YM155 (Woo, Min, Seo, &...…”
Section: Intracellular Anti‐apoptotic Proteins As Targeted Therapymentioning
confidence: 99%
“…21 We showed that when cancer cells adhere to mesothelial cells, the death receptor ligands expressed by mesothelial cells can activate death receptors expressed on cancer cells in a juxtacrine fashion, which results in apoptosis if 1 is present. 19 Thus, 1-mediated inhibition of c-FLIP expression restores death receptor-mediated cancer cell apoptosis during their adhesion to normal human mesothelial cells. 19 In a recent study, several analogues of 1 were synthesized to determine the role of the sulfonylacrylonitrile moiety and assess the potential of an amide replacement for the tert-butyl fragment of 1.…”
Section: ■ Introductionmentioning
confidence: 98%
“…19 Thus, 1-mediated inhibition of c-FLIP expression restores death receptor-mediated cancer cell apoptosis during their adhesion to normal human mesothelial cells. 19 In a recent study, several analogues of 1 were synthesized to determine the role of the sulfonylacrylonitrile moiety and assess the potential of an amide replacement for the tert-butyl fragment of 1. 22 While studies of these analogues pointed out the importance of the functional groups to the pro-apoptotic efficacy of 1, few of the analogues demonstrated increased efficacy in pancreatic, ovarian, or colon cancer cells compared with the parent compound.…”
Section: ■ Introductionmentioning
confidence: 98%
See 2 more Smart Citations